ANALYSIS OF THE EFFECT OF TRANSFORMATIONAL LEADERSHIP, CAREER ADAPTABILITY AND JOB EMBEDDEDNESS ON PERCEIVED CAREER SUCCESS: STUDY AT METAL MANUFACTURER COMPANY - Hendy Tannady (JURNAL EKOBIS DEWANTARA, 2023)
This study employs descriptive research techniques and non-probability sampling methods, namely, judgmental sampling techniques. 52 employees were given questionnaires to complete in order to collect primary data. Then secondary data can be obtained through supporting books and journals. Following that, the obtained data is processed using the SEM-PLS method. The Smart-PLS software is used to process the data from the pretest and main test. The study's findings show that transformational leadership positively affects perceptions of career success, career adaptability negatively affects perceptions of career success, transformational leadership positively affects job embeddedness, transformational leadership negatively affects work engagement, and transformational leadership positively affects perceived career success.